A inclusão de crianças com deficiência física no âmbito escolar: uma análise preliminar pela ótica de professores de sala de aula comum - Silva, Ruth Mariza Santos (Brasil, 2023)
This work aims to report, from the perspective of common classroom teachers, the inclusion of children with physical disabilities in the school environment, in a municipal school in the municipality of Parintins/Amazonas, also presenting if there are difficulties of teachers in the inclusion of children. with physical disabilities and what practices were used to monitor children in the classroom, the research subjects were enrolled students and teachers who work and deal directly with children with physical disabilities in the municipal school in the 1st to 5th year of elementary school , data were collected during observation at school and semi-structured interviews with teachers and was theoretically based on authors Gartner and Lipsky (1987), Pacheco (2007), Brazil (2015), Diniz (2022), among others who address the theme of the work. With regard to the results, when we analyze the teachers' understanding, it is clear that there are still difficulties that influence the view that the problem is centered on the person with a disability and not on the school context, however, adaptations are needed at school for inclusion. actually these students. However, this study aims to give the teacher a relevant role in the process of inclusion of students with physical disabilities, given all the difficulties faced.